The Adsorption Process using Custard Apple (Annona Squamosa) Seeds for the Removal of Chemical Oxygen Demand and Turbidity - Muhamad, Mimi Suliza; Teow, Chiew Yen; Hamidon, Nuramidah; Abdul Hamid, Nor Hazren (Penerbit UTHM, 2020)
River is considered as the most important freshwater source for human. Major rivers are used for drinking water supply, irrigation of agricultural lands, industrial and municipal water supplies, industrial and municipal water supplies. Water cannot be used directly from the sources due to the presence of contaminants [1]. Water used for drinking purpose should meet the water quality standards in the term of physical, biological and chemical characteristics. Therefore, effective water treatment is needed to improve the quality of water